2022
DOI: 10.31571/jpo.v11i2.4905
|View full text |Cite
|
Sign up to set email alerts
|

Status Dehidrasi Setelah Latihan Man to Man Pada Cabang Olahraga Futsal

Abstract: Pencapaian Status hidrasi yang baik apabila seorang atlet mengkonsumsi cairan yang cukup baik itu sebelum latihan, selama latihan dan setelah latihan. Kecukupan dalam pemberian cairan selama masa latihan sampai dengan pertandingan sangat penting dalam mempertahankan status hidrasi seorang atlet dimana mereka menjaga keseimbangan air dan elektrolit. Penelitian ini bertujuan untuk untuk mengetahui  status  dehidrasi  dengan Latihan man to man Pada Cabang Olahraga Futsal. Pada penelitian ini menggunakan metode   … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Effective strategies to address dehydration involve implementing fluid management interventions with careful monitoring of intake and output records (Muhammad et al, 2020). Ensuring adequate fluid administration throughout training and competitions plays a vital role in preserving hydration status (Haetami et al, 2022). Dehydration can adversely impact cardiovascular performance and disrupt the regulation of body thermoregulation (Kusuma, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Effective strategies to address dehydration involve implementing fluid management interventions with careful monitoring of intake and output records (Muhammad et al, 2020). Ensuring adequate fluid administration throughout training and competitions plays a vital role in preserving hydration status (Haetami et al, 2022). Dehydration can adversely impact cardiovascular performance and disrupt the regulation of body thermoregulation (Kusuma, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of dehydration extend to risks of obesity and reduced concentration (Sutarna, 2021). Maintaining proper hydration involves athletes consuming adequate fluids before, during, and after training sessions (Haetami et al, 2022). Previous research has demonstrated that dehydration can elevate pulse rates during exercise, indicative of potential adverse effects on physical performance and overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Managing dehydration involves implementing interventions that carefully monitor fluid intake and output (Muhammad et al, 2020). Ensuring adequate fluid administration from training periods to matches is crucial for maintaining hydration status (Haetami et al, 2022). Dehydration can impact the performance of cardiovascular organs and the regulation of body thermoregulation (Kusuma, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies show that dehydration will have a negative impact on health, including one's stamina and memory. (Haetami et al, 2022).…”
Section: Introductionmentioning
confidence: 99%